A Biomarker for Metastatic Colorectal Cancer and Treatment Goals - Aru W Suydoyo (Acta Medica Indonesiana)
The incidence of colorectal cancer (CRC) is rapidly increasing world-wide including in Indonesia and controversy not with standing, making it as the second most common malignancy (GLOBOCAN 2012). As with other cancers – more importantly with its adenoma-carcinoma sequence being one of the first to be elucidated by Vogelstein1 – its treatment and prognosis are determined by disease staging and molecular profile. Yet, identifying those for whom chemotherapy is indicated is still a challenge due to its histopathological heterogeneity; with special emphasis on stage II disease, for example, having a five-year survival that ranges from 87.5% for IIA to 58.4% in stage IIC. It is in such situation that predictive and prognostic markers are constantly being investigated. As one of the leading causes of cancer death in developed countries, much interest has grown in research in the development of biomarkers to improve the diagnostic process and to predict efficacy of chemotherapy.2 Only a few biomarkers are qualified as such, and the paucity of data has resulted in under- and overtreatment when relying only on the current TNM system. At present, only mutant KRAS, mutant BRAF, Microsatellite Instability (MSI) and the Oncotype DX® ColonCancer Assay are used in clinical practice. MSI and mutant KRAS are the established markers to date.3 But as the world is shifting towards personalized medicine (or “precision therapy” as is more frequently called), much work remains to be done.